The incidence of Soft Skills in Project Leaders of Work Teams (Nota: Artículo de Reflexión) (Dimensión Empresarial, 2025)
For those organizations that still manage traditional structures, where the security of face-to-face work is predominant, adapting to new work modalities, including remote work, is a challenging process of change in which managers need to learn and develop strategies and soft skills to lead successful teams, highlighting leadership and communication as key elements for the achievement of common objectives. For these purposes, a bibliographic review is proposed, finding evidence that allows inferring the incidence of soft skills in work teams. The results show that aspects such as emotional intelligence, negotiation/conflict resolution, teamwork and adaptability, together with communication and leadership, are necessary to manage teams both in face-to-face and virtual environments.
Keywords: Remote Teams; Leadership; Soft Skills